Redesign and analysis of a sorting blade for automated size-based sorting device - Yasser Suhaimi, Samsudin (Universiti Malaysia Perlis (UniMAP), 2016)
This paper discussed about redesign an blade for the sorting device which is to develop an efficient automated mechanical sorting system for the similar material but in different size. Nowdays we are facing problem with the rubbish separating or recycling problem.The Automated size based mechanical segregating system provides significant improvements in terms of efficiency and consistency in these segregating process. This device is designed to make recycling easier,in the hope that more people will take responsibility if it is less of an expense of time and effort. It is a new approach of recycling, which consider an unfortunate circumstance that people do not always have time or motivation to do the recycle. The project relates to the sorting according to their size. The machine should be able to identify the size of waste and it depends to the coil inside the container to separate it out. Wastes that want to be sort will be dumped into a closed container. In the container there are loops that will be wrapped around the container and wastes that want to be separated out will be attached to the loop. The loop will rotate to separate out the materials according to their size.. At the end of the loop there are holes where the collected waste materials will be dumped out. Due to the coil are not working efficienly,the coil are redesign.In this research, it is required to have knowledge in product design because have to design a mechanism which will be functioned automatically to sort similar materials of household wastes into respectively bin.With the redesigning of the coil, the analysis have been done with using anysys and solidwork. The coil are very suitable with the force and the simulation done.The conclusion is these coil are very suitable to the machine that separate the rubbish according to the size .The recycling industries are sustainable business because it does not consume much of the natural resources like the other types of manufacturing processes. These industries have the bright future in the future.